2021
DOI: 10.1093/cercor/bhab235
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanism Underlying the Sleep Deprivation-Induced Abnormal Bistable Perception

Abstract: Quality sleep is vital for physical and mental health. No matter whether sleep problems are a consequence of or contributory factor to mental disorders, people with psychosis often suffer from severe sleep disturbances. Previous research has shown that acute sleep deprivation (SD) can cause transient brain dysfunction and lead to various cognitive impairments in healthy individuals. However, the relationship between sleep disturbance and bistable perception remains unclear. Here, we investigated whether the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…Previous studies have found that SD-impaired memory was associated with the hippocampus. 35 , 36 Therefore, the reduced activation of the hippocampus in our research in the non-athlete group after SD occurred because SD damaged memory. In contrast, activation of the hippocampus was increased in the table tennis player group, possibly because the table tennis player group stored a large amount of episodic memory and abstract conceptual knowledge about table tennis.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Previous studies have found that SD-impaired memory was associated with the hippocampus. 35 , 36 Therefore, the reduced activation of the hippocampus in our research in the non-athlete group after SD occurred because SD damaged memory. In contrast, activation of the hippocampus was increased in the table tennis player group, possibly because the table tennis player group stored a large amount of episodic memory and abstract conceptual knowledge about table tennis.…”
Section: Discussionmentioning
confidence: 66%
“… 32 , 33 SD impairs memory which may relate to the activation in the frontoparietal areas, medial prefrontal cortex (mPFC), and hippocampus. 34 , 35 , 36 The increased risk-taking propensity of decision-making after SD is related to the left IFG and dlPFC, ventromedial prefrontal cortex (vmPFC). 37 , 38 , 39 , 40 These studies have documented the cognitive neuroscience mechanisms by which SD affects cognitive function in the general population; however, few studies evaluating the cognitive neuroscience mechanisms of SD affecting sports anticipation in athletes have existed.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large literature demonstrating evidence that sleep loss incurs temporary deficits in vigilance (measured by the psychomotor vigilance test) ( Banks and Dinges, 2007 ; Killgore, 2010 ; Kayser et al, 2022 ), attention ( Goel et al, 2009 ; Killgore, 2010 ; Kayser et al, 2022 ), emotional functioning ( Killgore, 2010 ; Kayser et al, 2022 ), mood ( Killgore, 2010 ; Kayser et al, 2022 ), and learning ( Goel et al, 2009 ; Killgore, 2010 ). There is also evidence of the effects of insufficient sleep on sensory perception ( Killgore, 2010 ; Zhou et al, 2022 ), appraisal ( Yoo et al, 2007a ; Killgore, 2010 ) and decision making ( Killgore, 2010 ; Kayser et al, 2022 ). The effects of SD on more executive processes are not as clear and involve different areas of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Influence of sleep deprivation on the leading basic modes. To assess whether the leading basic modes are affected by mental states, we applied the eigen-microstate analysis to the sleep deprivation dataset 50 . In this dataset, 19 participants underwent R-fMRI scanning during rested wakefulness and after sleep deprivation.…”
Section: Resultsmentioning
confidence: 99%
“…The eigen-microstate analysis is useful for extracting meaningful and fundamental spatial components (i.e., basic modes) underlying the temporal evolution of complex systems by incorporating spatial information over time 47,48 . Specifically, we applied this approach to R-fMRI data from healthy young adults from three datasets: the S900 release of the Human Connectome Project (HCP) 49 , the sleep-deprivation dataset 50 , and the Beijing Zang dataset 51 . First, we identified the leading basic modes that dominated the spontaneous fluctuations of BOLD signals and unraveled their cognitive significance.…”
mentioning
confidence: 99%